Optimizing formulation of fried rice-based snack supplemented with watermeal (Wolffia arrhiza (L.) Wimm.) and rice protein isolate powders using an I-optimal design: enhanced protein content and functional properties - Patcharabudsarakumkul, Kowit; Liamlaem, Sirintat; Hemathulin, Sukrichaya; Kapcum, Chutikarn; Itthivadhanapong, Pimchada; Somkhumphee, Yuphin; Piayura, Sumeth (Frontiers in Sustainable Food Systems, 2025)
This study aimed to optimize a fried snack formulation comprising Tubtim Chum Phae rice flour (RF; 60–79%), watermeal (Wolffia arrhiza, WM; 11–30%), and rice protein isolate (RP; 5–10%) to enhance protein content and functional properties, including total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity (AOA). Response Surface Methodology (RSM) with an I-optimal design was employed to predict the effects of ingredient ratios on all responses. The optimized formulation was validated through experiments, and its microstructure was analyzed using SEM. The amino acid profile was also determined. The RSM models accurately predicted the effects of ingredient ratios on all responses. Numerical optimization identified an optimal formulation consisting of 60.91% RF, 29.70% WM, and 8.39% RP, with validation experiments confirming strong agreement between predicted and actual values. The optimized snack exhibited 20.68% protein and improved functional properties. It showed a hardness of 14.04 N and a porous, non-uniform microstructure under SEM analysis. In addition, the amino acid profile, particularly in essential amino acids, was markedly enhanced compared to that of rice flour alone. These findings demonstrate that incorporating WM and RP using RSM is an effective strategy to improve the nutritional and antioxidant properties of rice-based snacks.